Efektifitas Pembesian pada Proyek Panbill Mall menggunakan Bar Bending Schedule SNI-2847-2019, BS-8666-2005, dan Linear Programming - Derwin Arifin; Ade Jaya Saputra; Amanatullah Savitri (Jurnal Manajemen Teknologi & Teknik Sipil, 2022)
The need for the amount of iron in a structural element becomes an important part of attention. Improper planning for iron needs will result in uncontrolled or excessive residual iron material. The effectiveness of iron is needed to minimize the amount of residual iron produced. This study aims to carry out the effectiveness of steel usage on the Panbill Mall Project based on the Bar Bending Schedule. The Bar Bending Schedule is carried out using the SNI-2847-2019, BS-8666-2005, and Linear Programming methods. The review of the reinforcement was carried out on the foundation structural elements (PC1 and PC2). Some data were collected such as steel length, quantity, and bending shape based on the structural drawings of the Panbill Mall project. From this data, calculations are made based on the Bar Bending Schedule with different references and methods. So that the minimum amount of iron will be obtained. Based on the results of the calculations and analysis carried out, it can be concluded that the Linear Programming method is the most effective method in calculating the iron based on the Bar Bending Schedule. Based on the results of residual iron calculated using SNI-2847-2019 and BS-8666-2005, the Linear Programming Method is more effective in reducing iron residues by 76% on P1C foundations and 92% on P2C foundations. These results can be used as a reference in calculating the iron based on the bar Bending Schedule effectively.